Pruritus as a Distinctive Feature of Type 2 Inflammation - Garcovich, Simone; Maurelli, Martina; Gisondi, Paolo; Peris, Ketty; Yosipovitch, Gil; Girolomoni, Giampiero (Vaccines (Basel), 2021)
Pruritus is a common symptom of several skin diseases, both inflammatory and neoplastic. Pruritus might have a tremendous impact on patients’ quality of life and strongly interfere with sleep, social, and work activities. We review the role of type-2 inflammation and immunity in the pathogenesis of chronic pruritic conditions of the skin. Type 2 cytokines, including IL-4, IL-13, thymic stromal lymphopoietin, periostin, IL-31, IL-25, and IL-33 are released by mast cells, innate lymphoid cells 2, keratinocytes, and type 2 T lymphocytes, and are master regulators of chronic itch. These cytokines might act as direct pruritogen on primary sensory neurons (pruriceptors) or alter the sensitivity to other itch mediators Type 2 inflammation- and immunity-dominated skin diseases, including atopic dermatitis, prurigo nodularis, bullous pemphigoid, scabies, parasitic diseases, urticaria, and Sézary syndrome are indeed conditions associated with most severe pruritus. In contrast, in other skin diseases, such as scleroderma, lupus erythematosus, hidradenitis suppurativa, and acne, type 2 inflammation is less represented, and pruritus is milder or variable. Th2 inflammation and immunity evolved to protect against parasites, and thus, the scratching response evoked by pruritus might have developed to alert about the presence and to remove parasites from the skin surface.